PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI MEDIATOR DAN JENIS INDUSTRI SEBAGAI MODERATOR PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2014 - Friska Aprilia Moina; Kamaliah Kamaliah; Desmiyawati Desmiyawati (Jurnal Ekonomi, 2016)
This study was conducted to test empirically 1) Effect of Disclosure of Corporate Social Responsibility (CSR) to the value of the Company, 2) Effect of Disclosure CSR to Profitability 3) Effect of Profitability of the Company Values, 4) Effect of Disclosure of CSR to value the Company through profitability and 5) Industry type Moderating Effect of CSR Disclosure of the value of the Company. Object under investigation is the manufacturing companies listed in Indonesia Stock Exchange 2013-2014 period. Tests conducted by the path analysis with a combination of moderation and mediation, using SPSS version 21. Prior to the tests, conducted prior test data normality and linearity test.The results of this study indicate that 1) Disclosure of CSR affect the value of the Company 2) Disclosure of CSR affect the profitability 3) Profitability affect the Company Value 4) Disclosure of CSR affect the Company's value through profitability 5) Industry Type Moderating Effect of CSR Disclosure of the value of the Company.